The association between the density of vaccination workers and immunization coverage in Zhejiang province, East China - Yu Hu; Yaping Chen; Ying Wang; Hu Liang; Huakun Lv (Taylor & Francis Group, 2021)
Background: We aimed to evaluate whether the density of vaccination workers was associated with the immunization coverage in Zhejiang province. Methods: The immunization coverage of measles-containing vaccine (MCV), the third dose of diphtheria, tetanus, and pertussis combined vaccine (DTP3), and the third dose of poliomyelitis vaccine (PV3) was selected as the dependent variables. Immunization coverage data of children aged 13-23 months were taken from the Zhejiang immunization information system (ZJIIS). The aggregate density of vaccination workers was an independent variable in one set of regressions, while the full-time and part-time vaccination workers were adopted separately in other sets. Results: The density of total vaccination workers was positively and significantly associated with the immunization coverage (MCV: AOR = 3.36; DTP3: AOR = 2.68; PV3: AOR = 2.37). However, when the effects of full-time vaccination workers and part-time vaccination workers were assessed separately, we only found that the density of full-time vaccination workers was positively and significantly associated with the immunization coverage (MCV: AOR = 5.59; DTP3: AOR = 4.13; PV3: AOR = 3.28). The proportion of migrant children < 7 years and Land area were found as negative and significant factors for immunization coverage. Conclusions: A higher density of vaccination workers could improve the availability of vaccination services and immunization coverage. We recommended that government or other non-government organization should, apart from vaccine-related assistance, focus their efforts on human resources for vaccination.